A case of childhood Brucellosis with neurological involvement and epididymo-orchitis - Saliha Kanik-Yuksek; Belgin Gulhan; Aslinur Ozkaya-Parlakay; Hasan Tezer (Journal of Infection in Developing Countries)
Brucellosis is a common zoonotic infection worldwide caused by Brucella species. Central nervous system involvement is a serious complication of brucellosis, and the clinical presentation is quite heterogeneous. The genitourinary system may be affected. Epididymo-orchitis is the most common type of urinary tract involvement, which can cause serious complications. Herein, we present a case of brucellosis in a child with a rare combination of epididymo-orchitis and neurobrucellosis not encountered previously in the literature.